THE THEOLOGY OF COMMUNITY SURVIVAL: A STUDY OF MIGRATION THEOLOGY, PENTECOSTALISM, AND WEST KALIMANTAN GAWAI CULTURE - Hasiholan, Anggi Maringan; Sitanggang, Asigor P; Usmanij, Petrus A. (Jurnal Lektur Keagamaan, 2023)
ABSTRACT Suffering is an inherent reality within Asian societies, stemming from various economic, political, social, cultural, and religious factors that contribute to the widespread poverty in Asia. While some individuals accept this suffering as a normal part of human life, others strive to escape the suffering. The concept of overcoming adversity is referred to as survival theology. This study explores the theology of survival through the lenses of migration theology, Pentecostalism, and Gawai Dayak culture. Employing a descriptive qualitative research method and a constructive theological approach, this study aims to understand how survival theology can be contextualized within these diverse frameworks. The findings reveal that communal unity serves as a powerful force to help individuals sustain suffering. Additionally, personal faith and trust provide additional for enduring hardhips as part of God’s plan. Keywords: Gawai West Kalimantan, Survival Theology, Contextual Studies, Pentecostalism   ABSTRAK Penderitaan merupakan realitas yang melekat dengan masyarakat, termasuk masyarakat Dayak. Faktor ekonomi, politik, sosial, budaya, dan agama menjadi penyebab suburnya kemiskinan. Merespons keadaan ini, ada yang menerimanya saja sebagai penderitaan wajar manusia, namun ada yang berjuang untuk keluar dari keadaan penderitaan. Konsep berjuang disebut dengan teologi bertahan hidup. Teologi bertahan hidup tercermin dalam teologi migrasi, Pentakostalisme, dan budaya Gawai Dayak. Tujuan penelitian ini untuk mengkaji teologi bertahan hidup dari teologi Migrasi dan Pentakostalisme yang dihubungkan dengan budaya Gawai Dayak. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan pendekatan teologi konstruktif. Hasil penelitian menunjukkan kebersamaan dalam komunitas menjadi kekuatan menghadapi penderitaan. Selain itu, iman dan kepercayaan pribadi juga memberikan kekuatan untuk menghayati proses penderitaan sebagai satu kesatuan rencana yang Allah berikan bagi setiap manusia.  Kata kunci: Gawai Kalimantan Barat, Teologi Bertahan hidup, Studi Kontekstual, Pentakostalisme